Photodynamic therapy for pododermatitis in penguins. Issue 4 (29th May 2014) - Sellera, Fábio Parra; Sabino, Caetano Padial; Ribeiro, Martha Simões; Fernandes, Loriê Tukamoto; Pogliani, Fabio Celidonio; Teixeira, Carlos Roberto; Dutra, Gustavo Henrique Pereira; Nascimento, Cristiane Lassálvia
<x xml:space="preserve">Abstract</x> Pododermatitis is currently one of most frequent and important clinical complications in seabirds kept in captivity or in rehabilitation centers. In this study, five Magellanic penguins with previous pododermatitis lesions on their footpad were treated with photodynamic therapy (PDT). All PDT treated lesions successfully regressed and no recurrence was observed during the 6‐month follow‐up period. PDT seems to be an inexpensive and effective alternative treatment for pododermatitis in Magellanic penguins encouraging further research on this topic. Zoo Biol. 33:353–356, 2014. © 2014 Wiley Periodicals, Inc.